?is iron deficiency anemia a risk factor for pneumonia in early childhood - غانم, سوالين; عبد المنعم غانم; مأمون حكيم (Latakia University Journal -Medical Sciences Series, 2022)
Lower respiratory tract infections and in particular pneumonia are considered one of the most important causes of childhood morbidity and mortality at the age of less than five years, and as an important health problem, due to the presence of several predisposing risk factors, including anemia specifically Iron deficiency anemia, it was necessary to investigate most of accused factors and to know the problem resulting from them for diagnosis and treat as early as possible. Objectives: The main objective: Studying the relationship of iron deficiency anemia with pneumonia among a sample of children admitted to the Pediatric Department at Tishreen University Hospital. Secondary objective: Study of other risk factors for pneumonia in children Methods: Successive children admitted to the Pediatric Department at Tishreen University Hospital with a history of clinically, radiologically and laboratory diagnosed pneumonia between the years (2020-2021) with ages ranging from (1 to 6 years) as a group of cases and patients of the same age and sex without pneumonia as a group of controls. Data were analyzed according to: sex, age, weight, height, presence or absence of pneumonia, detection of low birth weight, and peripheral blood smear findings. In addition to studying other risk factors, and their relationship with their recurrence of pneumonia. Nutritional status was assessed based on height and weight measurement and projected on the z-score index. The diagnosis for both study groups was based on clinical examination, medical history, radiological investigations and available laboratory analyzes. Results: The research sample included 50 children (33 males, 17 females) with a history of lung diagnosed clinically, radiologically and laboratory during the period (2020-2021), and the investigators included the inclusion criteria in the research. A sample of 50 children (27 male, 23 female) who did not have pneumonia was adopted as a control group. Where the percentage of males (60%) and females (40%) with Sex Ratio (M:F) = 1.5:1. The ages ranged between 1 to 6 years, and the average age was 2.99 ± 1.8 years. 60% of the research sample had anemia , of which (36%) was iron deficiency anemia, and deficiency anemia constituted a higher percentage in the case group (44%) compared to the control group (28%). Pneumonia was more common in males and in the age group (1 to 3 years).Among the city's population, and with the number of family members more than 5, pneumonia. cases represented (52%) compared to (20%) in the control group, there were no significant differences with respect to smoking between the two study groups. Regarding the presence of hypochromic micro-anaemia, it was higher in the case group (36%) compared to (10%) in the control group. The hemoglobin level (HB <11) in the case group was (56%) and in the control group (42%), where patients with cases who had anemia were at twice the risk of developing pneumonia compared to those who did not have anemia.